Perfil dos pacientes internados em uma unidade de terapia intensiva pediátrica de um hospital escola do interior de São Paulo - Alves, Maria Virginia Martim Faria Faddul [UNESP]; Bissiguini, Priscilla de Oliveira [UNESP]; Nitsche, Maria José Trevizani [UNESP]; Olbrich, Sandra Regina Leite Rosa [UNESP]; Luppi, Claudia Helena Bronzatto [UNESP]; Toso, Lis Amanda Ramos (My University, 2014)
The purpose of the study was to outline the profile of patients hospitalized at the Pediatric Intensive Care Unit of the Hospital das Clínicas de Botucatu - UNESP. This is a descriptive, cross-sectional and quantitative study. The data were extracted from the “Discharge, Admission and Death Register” of the unit of the patients hospitalized between January and December 2011. There was predominance of male children (54.4%) under one year of age (40,7%) were, with a mean length of stay of 5.46 days. Most of these children came from cities included in the DIR XI/SP in Botucatu (78.2%). The discharge contributed with 91.1% of the total discharges from the unit. Most admissions happened during the fall and winter, with the Immediate Post-Operative (IPO - 32.3%) and respiratory diseases (24.2%) as the most frequent causes. The profile of patients at the PICU makes it possible to elucidate individual aspects, family, social, demographic, seasonal, climatic, and, also, the clinical conditions, and, thus, comprehend the context of hospitalizations, in order to propose improvements on assistance, in an individualized and integral manner, for patients and their families.

El objetivo del estudio fue definir el perfil de los pacientes ingresados en la Unidad de Cuidados Intensivos Pediátricos del Hospital de las Clínicas de Botucatu - UNESP. Se trata de un estudio descriptivo, transversal y cuantitativo. Los datos utilizados fueron extraídos del "Libro de Alta, Admisión y Óbito" que pertenece a la unidad de los pacientes ingresados de enero a diciembre 2011. Hubo un predominio del sexo masculino (54,4%), franja de edad inferior a 1 año (40,7%) y con un promedio de permanencia de 5,46 días. La mayoría de estos niños era procedente de ciudades que hacen parte de la DIR XI/SP Botucatu (78,2%). El alta contribuyó con 91,1% del total de salidas de la unidad. La mayoría de las admisiones fue durante el otoño e inverno, teniendo como causas más frecuentes el Postoperatorio Inmediato (POI - 32,3%) y enfermedades respiratorias (24,2%). El perfil de los pacientes ingresados en la UCIP permite dilucidar aspectos individuales, familiares, sociales, demográficos, estacionales, climáticos y, también, de las condiciones clínicas y, así, entender el contexto de los ingresados, con el fin de proponer mejoras en la atención prestada, de manera individualizada e integral, para los pacientes y familiares.

O objetivo do estudo foi traçar o perfil dos pacientes internados na Unidade de Terapia Intensiva Pediátrica do Hospital das Clínicas de Botucatu - UNESP. Trata-se de um estudo descritivo, transversal e quantitativo. Os dados utilizados foram extraídos do “Livro de Alta, Admissão e Óbito” pertencente à unidade dos pacientes internados de janeiro a dezembro de 2011. Houve predomínio do sexo masculino (54,4%), faixa etária inferior a 1 ano (40,7%) e com uma média de permanência de 5,46 dias. A maioria dessas crianças era procedente de cidades que fazem parte da DIR XI/SP de Botucatu (78,2%). A alta contribuiu com 91,1% do total de saídas da unidade. A maioria das admissões foi durante o outono e inverno, tendo como causas mais frequentes o Pós-Operatório Imediato (POI - 32,3%) e doenças respiratórias (24,2%). O perfil dos pacientes internados na UTIP possibilita elucidar aspectos individuais, familiares, sociais, demográficos, sazonais, climáticos e, também, das condições clínicas e, assim, compreender o contexto das internações, no sentido de propor melhorias na assistência prestada, de maneira individualizada e integral, para os pacientes e familiares.
Profile of patients admitted in a pediatric intensive care unit of a hospital school in the countryside of São Paulo
Perfil de los pacientes admitidos en una unidad de cuidados intensivos pediátricos de un hospital escuela del interior de São Paulo
Keywords: Health profile; Patients; Child; Hospitalization; Intensive care unit; Respiratory tract diseases; Perfil de salud; Pacientes; Niño; Hospitalización; Unidad de cuidados intensivos; Enfermedades respiratorias; Perfil de saúde; Pacientes; Criança; Hospitalização; Unidade de terapia intensiva; Doenças respiratórias